The Strategic Role of Musical Storytelling as an Innovation in SKI Learning to Improve Students' Academic Achievement - Birini Sofiana; Sholikah (Aslim: Journal of Education and Islamic Studies, 2026)
This study aims to examine the role of Musical Storytelling as a form of learning innovation in improving student learning motivation and academic achievement in the subject of Islamic Cultural History (ISCH). The approach used was library research, reviewing, selecting, and analyzing various relevant literature sources on storytelling techniques, the use of music in learning, and the characteristics of ISCH learning. Data were analyzed using content analysis techniques to identify interconnections between concepts and develop a comprehensive theoretical synthesis. The results of the study indicate that the application of Musical Storytelling, which combines musical elements with storytelling techniques, can provide a more lively, engaging, and meaningful learning experience. This method not only increases student attention and engagement but also helps strengthen student understanding of historical material and encourages increased motivation and academic achievement. Therefore, Musical Storytelling can be used as an alternative ISCH learning strategy that is innovative, humanistic, and relevant to the needs of modern learning.